Geospatial Analysis of Hydrometeorological Dynamics for Managing Socio-economic and COVID-19 Threats in the Ossiomo Watershed, Nigeria - Innocent Ehiaguina Bello; Halilu A. Shaba (Faculty of Geography, Universitas Gadjah Mada, 2021)
The geographical occurrence and spread of the current novel COVID-19 pandemic are partly a function of the awareness, socio-economics, mobility, and health management practices in place. Ossiomo watershed in Edo State, Nigeria, is mainly a rural region with limited healthcare access and abundant water from River Ossiomo. One of the recommendations for preventing COVID-19 is washing hands with soap using running water. Thus, the novel COVID-19, a highly transmittable and pathogenic viral disease, requires effective management of available water resources for sustainable health development. The first confirmed case relating to the COVID-19 pandemic in Nigeria was announced on February 27, 2020, when an Italian citizen in Lagos tested positive for the virus. In most rural Africa, including Ossiomo, no pipe-borne water except rain harvesting for survival. Using GIS Inverse Distance Weighted (IDW) interpolation technique, the rainfall map produced (derived from a 31-year collated geo-located hydro-meteorological data - rainfall and discharge, covering the Ossiomo watershed) shows that rainfall decreases northward with minimum monthly precipitation of 18.8mm in January and to the south with a mean maximum rainfall of 339.0mm in July. NCDC records on Covid-19 were used to create Choropleth maps that revealed very low confirmed cases and relatively high deaths, though considered relatively low compared with global statistics. The Pearson Product Moment Correlation Coefficient (PPMCC) further indicates a strong correlation between rainfall and catchment discharge with r=0.717. With adequate socio-economic activities and water provisions, coupled with effective COVID-19 management practices, the pandemic may not linger in the study area.